THE INFLUENCE OF INDEPENDENT COMMISSIONERS, AUDIT COMMITTEES AND PROFITABILITY ON THE INTEGRITY OF LQ-45 INDEXED COMPANIES' FINANCIAL REPORT - Zara Tania Rahmadi; Muhammad Aria Wahyudi; Diah Nurdiana; Ahmad Nurdin Hasibuan (Jurnal Ekonomi, 2022)
This study aims to analyze the effect of independent commissioners, audit committees, and profitability on the integrity of financial statements. The research population is LQ-45 index companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The sampling technique used purposive sampling and obtained 34 companies, so the unit of analysis was 102. The study used moderate regression analysis with the IBM SPSS 25 program. The results of this study indicate that the audit committee has a positive effect on the integrity of financial statements. Meanwhile, independent commissioners and profitability have not proven to affect the integrity of financial statements